The relationship between social media exposure and sexual orientation of late adolescents - Renny Nova; Retno Lestari; Cicit Niara Suoth (PAGEPress Publications, 2024)
During adolescence, the development of sexual needs, the regulation of sexual orientation, and the decision to become a woman or a man are carried out to create a connection and form behavior leading to deviant sexual behavior. Sexual orientation becomes a person's identity in the environment and adolescents are expected to know the direction of attraction. The factors influencing sexual orientation are internal and external, such as exposure to social media. Therefore, this research aims to determine the relationship between social media exposure and late adolescent sexual orientation. A quantitative method is adopted using a cross-sectional design on 111 samples. The instruments used are the Intensity Scale of Social Media Use (SIPMS) and the Kinsey scale to measure exposure to social media and sexual orientation, respectively. The study's findings indicate a statistically significant correlation between social media exposure and sexual orientation in late adolescents, with a p-value of 0.040. In conclusion, education should be provided from an early age on sexual orientation and the anticipation of adolescents in fulfilling duties, resulting in a process of self-development within the social environment.